Corneal properties in children with congenital isolated growth hormone deficiency - Pinar Nalcacioglu-Yuksekkaya; Emine Sen; Ufuk Elgin; Mumin Hocaoglu; Faruk Ozturk; Sebahat Agladıoglu Yilmaz; Havva Nur Kendirci; Semra Çetinkaya; Zehra Aycan (International Journal of Ophthalmology, 2014)
AIM:To compare the corneal parameters of children with congenital isolated growth hormone deficiency and healthy subjects.METHODS: In this cross-sectional, prospective study, 50 cases with growth hormone (GH) deficiency treated with recombinant GH and 71 healthy children underwent a complete ophthalmic examination. The corneal hysteresis (CH), corneal resistance factor (CRF), Goldmann-correlated intraocular pressure (IOPg) and corneal-compensated intraocular pressure (IOPcc) were measured with the Ocular Response Analyzer (ORA). Central corneal thickness (CCT) was measured by a ultrasonic pachymeter.RESULTS: The mean age was 13.0±3.0 years in the GH deficiency group consisting of 21 females and 29 males and 13.4±2.4 years in the healthy children group consisting of 41 females and 30 males. There was no statistically significant difference between the groups for gender or age (Chi-square test, P=0.09; independent t-test, P=0.28, respectively). The mean duration of recombinant GH therapy was 3.8±2.4y in the study group. The mean CH, CRF, IOPg and IOPcc values were 11.0±2.0, 10.9±1.9, 15.1±3.3, and 15.1±3.2 mm Hg respectively in the study group. The same values were 10.7±1.7, 10.5±1.7, 15.2±3.3, and 15.3±3.4 mm Hg respectively in the control group. The mean CCT values were 555.7±40.6, 545.1±32.5 µm in the study and control groups respectively. There was no statistically significant difference between the two groups for CH, CRF, IOPg, IOPcc measurements or CCT values (independent t-test, P=0.315, 0.286, 0.145, 0.747, 0.13 respectively).CONCLUSION: Our study suggests that GH deficiency does not have an effect on the corneal parameters and CCT values. This observation could be because of the duration between the beginning of disease and the diagnosis and beginning of GH therapy.